Pembuatan dan Pelatihan Administrator Website pada Dinas Kesehatan Kabupaten Ogan Komering Ulu - Budi Kurniawan; Muhammad Romzi (Jurnal Pengabdian Masyarakat (ABDIRA), 2022)
Information technology, especially the internet and websites, is one of the results of rapidly growing information technology. The Health Office of Ogan Komering Ulu (OKU) is currently using the website to disseminate information to stakeholders without following the rules regulated by the regulations in e-Aspiration 2021. Therefore, the Health Office has made changes to the content of the website from design to programming, for that the website manager The Health Office encourages the Office to seek human resources who have the expertise to create websites as needed. Based on the problems above, PKM was held for the manufacture and training of website administrators for the Health Office administrator. The target of this training is the website administrator of the Health Office. Community service uses several methods, namely the method of making and training on how to use the Website. Through this service activity, we produce a website that is in accordance with e-Aspiration 2021 which can be accessed at https://dinkes.okukab.go.id/. Through this PKM, administrators can manage their own website and stakeholders can find out information and activities carried out by the OKU Health Office.